(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2001)
Late Wordian (Guadalupian) brachiopods from Member 2 of the Panjshah Formation in the Karakorum (N Pakistan) are described. The brachiopod assemblage, dated by the associated fusulinids and conodonts, consists of 29 genera (3 of which are questionable and 1 unidentifiable) of the orders Productida, Orthida, Rhynchonellida, Athyridida, Spiriferida and Terebratulida. Hunzininae, a new subfamily of the Spiriferellidae is proposed; it includes Darbandia n. gen., with type species D. vagabunda n. sp. and Elivina chapursani n. sp. A third new species is assigned to the genus Anchorhynchia of the family Wellerellidae: A. cimmerica n. sp. A quantitative biostratigraphic analysis demonstrates two major faunal changes in the Elivina chapursani- Chapursania tatianae Assemblage Zone of the upper part of Member 2, which are not strictly linked to lithological changes. This biozone is correlated with the brachiopod faunas of the Gnishik Formation of Armenia and those of the basal Takhtabulak Formation of SE Pamir. The faunal elements of the Elivina chapursani- Chapursania tatianae Assemblage Zone are an admixture of wide-ranging, Tethyan (particularly abundant), Gondwanan and endemic (Cimmerian) genera, representing a transitional fauna and a biostratigraphic tool for intercontinental correlation, which are particularly problematic in this time interval. The Panjshah transitional fauna demonstrates the persistence of the Transhimalayan Province of the Cimmerian Region into the late Guadalupian, which originated at the end of the Cisuralian and occupied Armenia, Central Afghanistan, Karakorum and SE Pamir. It provides also some insights into the biodiversity pattern before the mass extinction at the end of the Guadalupian, and suggests that this event was as rapid as the end- Permian mass extinction, at least in Central Asia.